Analytical estimate for low‐altitude ENA emissivity. Issue 2 (6th February 2016) - Goldstein, J.; Bisikalo, D. V.; Shematovich, V. I.; Gérard, J.‐C.; Søraas, F.; McComas, D. J.; Valek, P. W.; LLera, K.; Redfern, J.
Abstract: We formulate the first analytical model for energetic neutral atom (ENA) emissivity that partially corrects for the global viewing geometry dependence of low‐altitude emissions (LAEs) observed by Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS). The emissivity correction requires the pitch angle distribution (PAD) and geophysical location of low‐altitude ENAs. To estimate PAD, we create an energy‐dependent analytical model, based on a Monte Carlo simulation. We account for energy binning by integrating model PAD over each energy bin. We account for finite angular pixels by computing emissivity as an integral over the pitch angle range sampled by the pixel. We investigate location uncertainty in TWINS pixels by performing nine variations of the emissivity calculation. Using TWINS 2 ENA imaging data from 1131 to 1145 UT on 6 April 2010, we derive emissivity‐corrected ion fluxes for two angular pixel sizes: 4° and 1°. To evaluate the method, we compare TWINS‐derived ion fluxes to simultaneous in situ data from the National Oceanic and Atmospheric Administration (NOAA) 17 satellite. The TWINS‐NOAA agreement for emissivity‐corrected flux is improved by up to a factor of 7, compared to uncorrected flux. The highest 1° pixel fluxes are a factor of 2 higher than for 4° pixels, consistent with pixel‐derived fluxes that are artificially low because subpixel structures are smoothed out, and indicating a possible slight advantage to oversampling the instrument‐measured LAE signal. Both TWINS and NOAA ion fluxes decrease westward of 2000 magnetic local time. The TWINS‐NOAA comparison indicates that the global ion precipitation oval comprises multiple smaller‐scale (3–5° of latitude) structures. Key Points: Analytical model of low‐altitude ENA emissivity depends on local PAD and geometry Emissivity‐corrected TWINS ion fluxes evaluated using in situ NOAA data Global ion precipitation oval comprises multiple smaller‐scale structures